1986
DOI: 10.3382/ps.0651291
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Combined Effects of Aflatoxin and Deoxynivalenol (DON, Vomitoxin) in Broiler Chickens

Abstract: The individual and combined effects of aflatoxin and deoxynivalenol (DON) were evaluated in young broiler chickens (Hubbard X Hubbard). The experimental design was a 2 X 2 factorial with treatments of 0 and 2.5 micrograms of aflatoxin/g of feed (ppm) and 0 and 16 micrograms of DON/g of feed. The broilers were maintained on these dietary treatments from hatching to 3 weeks of age in electrically heated batteries with feed and water available ad libitum. The aflatoxin treatment significantly (P less than .05) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 15 publications
4
63
0
Order By: Relevance
“…In the present study, significant Tables 5 and 6). These findings agreed with the other reports that explain the suppressive effects of AF on haematopoiesis and immune responses (Huff et al, 1986;Oguz et al, 2003). The increase in heterophil counts suggested that the toxin was eliciting inflammatory response of chicks (Kececi et al, 1998).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, significant Tables 5 and 6). These findings agreed with the other reports that explain the suppressive effects of AF on haematopoiesis and immune responses (Huff et al, 1986;Oguz et al, 2003). The increase in heterophil counts suggested that the toxin was eliciting inflammatory response of chicks (Kececi et al, 1998).…”
Section: Discussionsupporting
confidence: 83%
“…AFB1 consumption during growth can lead to immune tissue atrophy, reducing relative weights of the bursa, spleen and thymus [120,122,134,139,[149][150][151][152]. Increases in relative spleen weight have also been observed during aflatoxicosis [117,120,[153][154][155][156]. In young chickens, tissue changes are concomitant to the development of histopathological lesions.…”
Section: Immunotoxicitymentioning
confidence: 99%
“…In spite of this, comparison of these concentrations to those used in laboratory experiments suggested that these cranes could have been subject to chronic mycotoxic effects. These negative effects include growth retardation, tumor development, and immunotoxicity, thus increasing crane susceptibility to predation and disease (Carnaghan, 1965;Choudhury, 1971;Huff et al, 1986;Kamalavenkatesh et al, 2005). Moreover, although low mycotoxin concentrations do not cause morbidity in controlled laboratory settings, it might reduce the survival probability of wild species that rely on highly efficient metabolic systems to cope with extreme environments, such as winter conditions (Oberheu and Dabbert, 2001).…”
Section: Discussionmentioning
confidence: 99%